A method for controlling the reaction interface oxide layer of a thick-gauge 800mpa-grade hot-dip galvanized dual-phase steel

CN122669177BActive Publication Date: 2026-10-16BENGANG STEEL PLATES CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611162927.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-16
Estimated Expiration
2046-08-03

AI Technical Summary

Technical Problem

[0004]现有技术中,虽部分工艺尝试通过调整炉内露点、气氛及氧含量等参数,实现合金元素的内部氧化以减少表面氧化,但对于厚规格产品而言,其厚度带来的热传导不均、合金元素扩散路径延长等问题,使得氧化层控制难度显著提升,现有参数调控手段难以精准适配厚规格产品的界面反应特性,无法有效平衡合金元素氧化与镀锌界面结合性能的关系,仍难以彻底解决表面漏镀、锌层附着力不足等核心问题

Benefits of technology

满足汽车及高端装备制造领域对高品质钢材的严苛需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122669177B_ABST
    Figure CN122669177B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of steel plate production, and particularly relates to a method for controlling the reaction interface oxide layer of a thick-gauge 800MPa-grade hot-dip galvanized dual-phase steel, comprising the following steps: 1) hot rolling: adopting a multi-stage hot rolling cooling process; 2) pickling: the strip speed is 80-85m / min, and the acid liquid temperature is 82-85℃; 3) pretreatment: surface cleaning and drying treatment are performed on the strip steel; 4) annealing reduction: gradient heating is adopted for heating, and then cooling to 690-700℃; H2 and N2 are introduced into the furnace; pre-oxidation is performed by introducing nitrogen-oxygen mixed gas, and the humidification dew point is set to -5℃ to -10℃; 5) hot-dip galvanizing: the annealed strip steel is immersed in molten zinc liquid, the zinc liquid temperature is 455-465℃, and the immersion galvanizing time is 4-6s; 6) post-treatment: air knife blowing is adopted. Advantage: the present application can effectively inhibit the generation of harmful interface oxide layers, obtain a thin and dense aluminum-containing inhibition layer, and improve the coating adhesion and surface quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of steel plate production technology, and in particular relates to a method for controlling the oxide layer at the reaction interface of 800MPa grade hot-dip galvanized duplex steel. Background Technology

[0002] With the rapid development of the modern automotive industry towards weight reduction, energy conservation, and high safety, high-strength hot-dip galvanized duplex steel has become one of the core choices for automotive body materials due to its excellent strength-toughness ratio, low yield strength ratio, and good corrosion resistance. Among them, 800MPa grade hot-dip galvanized duplex steel, which can balance the requirements of lightweighting and structural strength, has become a core material for key parts such as body structural components and chassis load-bearing components due to its high strength and excellent corrosion resistance, and its application in the body-in-white manufacturing field continues to increase. However, in the production process of thick-gauge 800MPa grade hot-dip galvanized duplex steel, the control of the oxide layer at the reaction interface has always been a key challenge restricting product quality, directly affecting the adhesion and forming performance of the zinc layer on the hot-dip galvanized surface, becoming a technical bottleneck that the industry urgently needs to overcome.

[0003] In the production process of thick-gauge 800MPa grade hot-dip galvanized duplex steel, alloying elements such as Cr, Mn, and Si need to be added to ensure the strength of the steel. However, in the high-temperature environment of the annealing furnace in the galvanizing line, these alloying elements readily react with small amounts of water vapor or oxygen in the protective reducing gas, forming non-uniform silicon and manganese oxide particles or even continuous oxide films on the surface of the steel substrate. Figures 1-9 Because these oxides are non-wetting to molten zinc, they directly hinder the contact between the molten zinc and the steel substrate, resulting in insufficient coating adhesion and numerous uncoated defects, severely restricting product surface quality and service performance. The formation of this interfacial oxide layer is closely related to multiple factors such as the annealing furnace atmosphere, selective oxidation of alloying elements, and interfacial reaction kinetics, and has become a technical bottleneck that the industry urgently needs to overcome.

[0004] In existing technologies, although some processes attempt to reduce surface oxidation by adjusting parameters such as dew point, atmosphere, and oxygen content in the furnace to achieve internal oxidation of alloying elements, for thick products, the uneven heat conduction and extended diffusion paths of alloying elements caused by the thickness significantly increase the difficulty of oxide layer control. Existing parameter control methods are difficult to accurately adapt to the interface reaction characteristics of thick products, and cannot effectively balance the relationship between alloying element oxidation and zinc plating interface bonding performance. Therefore, it is still difficult to completely solve core problems such as surface plating defects and insufficient zinc layer adhesion.

[0005] In addition, to suppress the ferrite and bainite phase transformation of thick 800MPa grade hot-dip galvanized duplex steel during the zinc bath galvanizing process at 460℃, it is necessary to further increase the amount of alloying elements added. This to some extent exacerbates the risk of selective oxidation of alloying elements, resulting in a more complex composition and structure of the oxide layer at the reaction interface, further increasing the difficulty of precise control of the oxide layer.

[0006] Therefore, existing technologies are insufficient to meet the demand for precise control of the oxide layer at the reaction interface of thick 800MPa grade hot-dip galvanized duplex steel. There is an urgent need to develop a targeted and highly adaptable oxide layer control method to effectively inhibit the formation of harmful surface oxide layers, ensure the bonding quality of the galvanized interface, improve the product performance and production stability of thick 800MPa grade hot-dip galvanized duplex steel, and meet the stringent requirements of the automotive industry for high-strength and high-quality steel. Summary of the Invention

[0007] To overcome the shortcomings of the prior art, the purpose of this invention is to provide a method for controlling the oxide layer at the reaction interface of thick 800MPa grade hot-dip galvanized duplex steel. By precisely controlling the annealing process, reducing atmosphere and zinc liquid composition, the thickness, composition and structure of the oxide layer at the reaction interface can be controlled, thereby improving the coating adhesion, corrosion resistance and forming stability.

[0008] To achieve the above objectives, the present invention provides the following technical solution: A method for controlling the oxide layer at the reactive interface of thick 800MPa grade hot-dip galvanized duplex steel includes the following steps: 1) Hot rolling: A multi-stage hot rolling cooling process is adopted; 2) Pickling: belt speed is 80-85 m / min, acid temperature is 82-85℃; 3) Pretreatment: The strip steel is surface cleaned and dried at a temperature of 120-150℃ for 5-8 minutes. 4) Annealing and Reduction: The strip steel is fed into a continuous annealing furnace at a speed of 50–52 m / min. A gradient heating process is adopted, first heating to 780–820℃ at 15–20℃ / s, then heating to 820–845℃ at 3–5℃ / s, and holding for 3–5 s; subsequently cooling to 690–700℃ at 10–12℃ / s, and holding for 2–3 s; 15%–18% H2 and 82%–85% N2 by volume are introduced into the furnace, and the dew point is controlled at -40℃ to -45℃; then it enters the pre-oxidation stage, using a nitrogen-oxygen mixed gas with a flow rate of 15–18 m³ / min. 3 / h, the humidification dew point is set to -5℃~-10℃, and the grate dew point is set to -25℃~-30℃; 5) Hot-dip galvanizing: The annealed strip steel is immersed in molten zinc at a temperature of 455-465℃ for 4-6 seconds. 6) Post-treatment: Air knife purging is used, with an air knife pressure of 0.08-0.12 MPa and a distance of 10-15 mm between the air knife and the strip. Then, air cooling is carried out at a rate of 15-30℃ / s to 300-350℃, and then water cooling is carried out at a rate of 30-50℃ / s to room temperature.

[0009] The hot rolling process involves heating at a temperature of 1200–1250°C, followed by rough rolling and then finish rolling. The initial rough rolling temperature is 1070–1120°C, and the final finish rolling temperature is 840–860°C. The coiling process is carried out in two stages: the first stage involves water cooling to 600–620°C, followed by air cooling to 550–560°C, and the second stage involves water cooling to 200–240°C before coiling.

[0010] The chemical composition of the zinc liquid, by weight percentage, includes: Zn ≥ 99.5%, Al 0.20%~0.25%, Pb ≤ 0.003%, with the balance being unavoidable impurities.

[0011] The zinc solution also contains 30-50 ppm of rare earth element La.

[0012] The thickness of the hot-dip galvanized duplex steel sheet is 2.5 to 3.5 mm.

[0013] The chemical composition of the hot-dip galvanized duplex steel, by weight percentage, includes: C: 0.11%~0.15%, Mn: 1.70%~2.00%, Si: 0.35%~0.50%, P≤0.025%, Cr: 0.35%~0.52%, Nb: 0.015%~0.026%, Als: 0.020%~0.038%, with the balance being Fe. The microstructure of the hot-dip galvanized duplex steel is a ferrite-martensite dual-phase structure, with a martensite volume fraction of 20%~40%.

[0014] The nitrogen-oxygen mixture contains, by volume percentage: 20%–25% oxygen, with the remainder being nitrogen and unavoidable impurity gases.

[0015] Compared with the prior art, the beneficial effects of the present invention are: To meet the stringent requirements of the automotive and high-end equipment manufacturing sectors for high-quality steel.

[0016] This invention utilizes the synergistic effect of hot-rolling gradient cooling, galvanizing gradient annealing, and precise reducing atmosphere to form a uniform and dense pre-reduced layer on the strip steel surface, suppressing the disordered growth of the oxide layer from the source. By optimizing the zinc bath composition and immersion parameters, the interfacial reaction is controlled, significantly improving the adhesion between the coating and the substrate. Testing shows that the coating adhesion meets adhesive requirements, satisfying the stringent requirements for high-strength, thick-gauge duplex steel. Furthermore, the process parameters of this invention are stable and controllable, suitable for large-scale industrial production, effectively solving the problems of insufficient precision in oxide layer control and poor coating adhesion in existing technologies, providing technical support for the high-quality production of thick-gauge 800MPa grade hot-dip galvanized duplex steel. The process method described in this invention can greatly control the enrichment of Mn elements at the reaction interface, obtaining a thin and dense aluminum-containing inhibition layer. Attached Figure Description

[0017] Figure 1 This is a cross-sectional microstructure image (scanning electron microscope backscattered electron image) of a 2.5mm thick 800MPa grade strip produced by conventional methods.

[0018] Figure 2 This is an elemental line scan of 2.5mm thick 800MPa grade strip steel produced using conventional methods. Figure 1 (Element O).

[0019] Figure 3 This is an elemental line scan of 2.5mm thick 800MPa grade strip steel produced using conventional methods. Figure 2 (Mn element).

[0020] Figure 4 This is an elemental line scan of 2.5mm thick 800MPa grade strip steel produced using conventional methods. Figure 3 (All elements).

[0021] Figure 5 This is a cross-sectional microstructure image (scanning electron microscope secondary electron image) of a 2.5mm thick 800MPa grade strip produced by conventional methods.

[0022] Figure 6 This is an elemental surface scan of 2.5mm thick 800MPa grade strip steel produced using conventional methods. Figure 1 (Element O).

[0023] Figure 7 This is an elemental surface scan of 2.5mm thick 800MPa grade strip steel produced using conventional methods. Figure 2 (Al element).

[0024] Figure 8 This is an elemental surface scan of 2.5mm thick 800MPa grade strip steel produced using conventional methods. Figure 3 (Mn element).

[0025] Figure 9 This is a surface morphology image (scanning electron microscope secondary electron image) of a 2.5mm thick, 800MPa grade steel strip suppression layer produced by conventional methods.

[0026] Figure 10 This is a cross-sectional microstructure image (scanning electron microscope backscattered electron image) of a 2.5mm thick 800MPa grade strip produced by the method of this invention.

[0027] Figure 11 This invention relates to the elemental line scan of 2.5mm thick 800MPa grade strip steel produced by the method of this invention. Figure 1 (Element O).

[0028] Figure 12 This invention relates to the elemental line scan of 2.5mm thick 800MPa grade strip steel produced by the method of this invention. Figure 2 (Mn element).

[0029] Figure 13 This invention relates to the elemental line scan of 2.5mm thick 800MPa grade strip steel produced by the method of this invention. Figure 3 (All elements).

[0030] Figure 14 This is a cross-sectional microstructure diagram (scanning electron microscope secondary electron image) of a 2.5mm thick 800MPa grade strip steel produced by the method of this invention.

[0031] Figure 15 This is an elemental surface scan of 2.5mm thick 800MPa grade strip steel produced by the method of this invention. Figure 1 (Element O).

[0032] Figure 16 This is an elemental surface scan of 2.5mm thick 800MPa grade strip steel produced by the method of this invention. Figure 2 (Al element).

[0033] Figure 17 This is an elemental surface scan of 2.5mm thick 800MPa grade strip steel produced by the method of this invention. Figure 3 (Mn element).

[0034] Figure 18 This is a surface morphology diagram of the 2.5mm thick 800MPa grade steel strip suppression layer produced by the method of this invention.

[0035] Figure 19 This is a hot rolling process curve diagram of the present invention.

[0036] Figure 20 This is a hot rolling process curve diagram of Example 1. Detailed Implementation

[0037] The present invention will now be described in detail with reference to the accompanying drawings, but it should be noted that the implementation of the present invention is not limited to the following embodiments.

[0038] A method for controlling the oxide layer at the reaction interface of thick-gauge 800MPa grade hot-dip galvanized duplex steel is disclosed. The hot-dip galvanized duplex steel sheet has a thickness of 2.5–3.5 mm and a matrix structure consisting of ferrite and martensite, with a martensite volume fraction of 20%–40%. By precisely controlling the annealing process, reducing atmosphere, and zinc bath composition, the thickness, composition, and structure of the oxide layer at the reaction interface are precisely controlled, thereby improving coating adhesion and product quality. The method includes the following steps: 1. Hot Rolling: To minimize the surface enrichment of Si and Mn oxides in subsequent rolling processes, a multi-stage hot rolling cooling process is employed. This involves controlling the temperature range to ensure the desired microstructure characteristics, and rapid cooling to facilitate structural separation of the oxide layer from the substrate, providing favorable conditions for subsequent pickling processes. See [link to relevant documentation]. Figure 19 A multi-stage hot rolling cooling process is adopted: The heating temperature is 1200-1250℃. The process involves rough rolling followed by finish rolling. The initial rough rolling temperature is 1070-1120℃, and the final finish rolling temperature is 840-860℃. The coiling is carried out in two stages of water cooling. The first stage involves water cooling to 600-620℃ and air cooling to 550-560℃. The second stage involves water cooling to 200-240℃ before coiling.

[0039] 2. Pickling: To improve the removal of iron oxide scale, a belt speed of 80-85 m / min and an acid temperature of 82-85℃ are adopted. This process is highly related to the strip steel composition, hot rolling process, and the thickness and composition of the iron oxide scale in the preceding process. Therefore, the settings should be made separately for the composition and hot rolling process. Too high or too low belt speed and acid temperature will result in over-pickling or under-pickling of the strip steel, which will affect the surface quality of subsequent galvanizing.

[0040] 3. Pretreatment: The surface of the 800MPa grade duplex steel strip is cleaned to remove oil and impurities, and then dried. The drying temperature is controlled at 120-150℃ for 5-8 minutes to ensure that the surface of the strip is dry and clean, laying the foundation for subsequent processes.

[0041] 4. Annealing and Reduction: The dried strip steel is fed into a continuous annealing furnace at a speed of 50–52 m / min. A gradient heating process is used, heating the strip steel to 780–820℃ at a heating rate of 15–20℃ / s, then heating it to 820–845℃ at a heating rate of 3–5℃ / s and holding it at that temperature for 3–5 s to ensure complete austenitization of the duplex steel matrix. Subsequently, it is cooled to 690–700℃ at a cooling rate of 10–12℃ / s and held for 2–3 s to promote the uniform formation of the ferrite and martensite duplex structure. The annealing furnace is purged with 15%–18% H2 and 82%–85% N2 by volume, and the dew point is controlled at -40℃ to -45℃. By precisely controlling the atmosphere and temperature, and reducing the holding time in the high-temperature range, the temperature gradient of the strip is controlled along its thickness, ensuring that the surface temperature of the strip remains consistently higher than that of the core. This causes surface volume expansion, creating compressive stress from the surface inward, compressing the diffusion channels of Si and Mn elements along the grain boundaries, and suppressing the tendency of element enrichment on the surface during heating. A pre-oxidation process is added, using a nitrogen-oxygen mixed gas (with an oxygen content of 20%–25%), with a gas flow rate of 15–18 m³ / h. 3 The humidification dew point is set to -5℃ to -10℃. This process is mainly formulated based on the specific strip steel composition and previous processes. Due to the manganese and silicon content of the strip steel, the structure and thickness of the pre-oxidation layer directly affect the settings of the subsequent reduction section and the strip speed. The pre-oxidation process forms a uniform oxide film on the surface of the strip steel. This film is reduced by hydrogen in the subsequent reduction section to a porous active iron layer, which can both inhibit the re-diffusion of manganese and silicon elements and ensure good wettability of the zinc liquid to the strip steel surface. The grate dew point is set to -25℃ to -30℃ to ensure control of zinc ash on the strip steel surface and coating adhesion.

[0042] 5. Hot-dip galvanizing: The annealed steel strip is rapidly immersed in molten zinc, with the zinc bath temperature controlled at 455–465℃ and the immersion time controlled at 4–6 seconds. The chemical composition of the zinc bath, by weight percentage, includes: Zn ≥ 99.5%, Al 0.20%–0.25%, Pb ≤ 0.003%, with the balance being unavoidable impurities. Precise addition of aluminum allows for preferential reaction with trace amounts of residual oxygen on the steel strip surface, forming a thin and uniform interfacial reaction layer. Simultaneously, it inhibits excessive reaction between the zinc bath and the substrate, preventing oxide layer thickening. Strict control of the immersion time reduces the reaction duration between the steel strip and the zinc bath, further controlling the oxide layer growth rate.

[0043] Rare earth element La (30-50 ppm) can also be added to the zinc bath. Rare earth elements can refine the grains of the interfacial reaction layer, improve the density and stability of the oxide layer, and further enhance the adhesion between the coating and the substrate.

[0044] 6. Post-processing: After the strip steel exits the zinc pot, it is purged with an air knife. The air knife pressure is controlled at 0.08-0.12MPa, and the distance between the air knife and the strip steel is 10-15mm. Through precise air knife parameters, excess zinc liquid is removed from the surface of the strip steel. Then it is cooled to room temperature to complete the preparation of thick 800MPa grade hot-dip galvanized duplex steel.

[0045] The cooling process employs a combination of air cooling and water cooling. First, the temperature is cooled to 300-350°C with air at a rate of 15-30°C / s, and then cooled to room temperature with water at a rate of 30-50°C / s. This ensures uniform cooling and meets the required microstructure characteristics, preventing stress cracks in the interface oxide layer caused by uneven cooling.

[0046] Example 1:

[0047] The method for controlling the oxide layer at the reactive interface of 2.5mm thick 800MPa grade hot-dip galvanized duplex steel includes the following main steps: 1. Hot rolling: The heating temperature is 1250℃. The rolling process involves rough rolling followed by finish rolling. The initial rough rolling temperature is 1080℃, and the final finish rolling temperature is 840℃. The coiling is carried out in two stages of water cooling. The first stage involves water cooling to 600℃ and air cooling to 560℃. The second stage involves water cooling to 220℃ before coiling.

[0048] 2. Pickling: The belt speed is controlled at 82 m / min, and the acid temperature is 84℃.

[0049] 3. Pre-treatment: Clean the surface of the strip steel to remove oil and impurities, and then dry it at 140℃ for 6 minutes to ensure that the strip steel surface is dry and clean, laying the foundation for subsequent processes.

[0050] 4. Annealing: The dried strip steel is fed into a continuous annealing furnace at a speed of 50 m / min. A gradient heating process is used, heating the strip steel to 810℃ at a heating rate of 18℃ / s, then heating it to 845℃ at a heating rate of 4℃ / s and holding it for 5 seconds to ensure complete austenitization of the duplex steel matrix. Subsequently, it is cooled to 700℃ at a cooling rate of 12℃ / s and held for 3 seconds to promote the uniform formation of the ferrite and martensite duplex structure. 18% hydrogen by volume is introduced into the annealing furnace for reduction, with the dew point controlled at -43℃ and nitrogen accounting for 82% of the volume. A pre-oxidation process is added, with a pre-oxidation gas flow rate of 15 m³ / min. 3 / hour, nitrogen and oxygen mixed gas, humidification dew point set to -8℃, grate dew point set to -30℃, to ensure zinc ash control and coating adhesion on the strip surface.

[0051] 5. Hot-dip galvanizing: The annealed steel strip is rapidly immersed in molten zinc at a temperature controlled at 462℃ for 6 seconds. The zinc bath composition by weight percentage is: Zn 99.5%, Al 0.24%, Pb 0.001%, with the balance being unavoidable impurities. 40 ppm of rare earth element La is also added to the zinc bath.

[0052] 6. Post-processing: After the strip steel exits the zinc bath, it is purged with an air knife at a pressure controlled at 0.11 MPa and a distance of 14 mm between the air knife and the strip steel to remove excess zinc from the surface. It is then first air-cooled to 310°C at a rate of 18°C / s, and then water-cooled to room temperature at a rate of 35°C / s to complete the preparation of thick-gauge 800MPa grade hot-dip galvanized duplex steel.

[0053] The chemical composition of the 800MPa grade hot-dip galvanized duplex steel substrate, by weight percentage, includes: C: 0.13%, Mn: 1.85%, Si: 0.42%, P: 0.020%, Cr: 0.45%, Nb: 0.019%, Als: 0.025%, balance Fe.

[0054] In this embodiment, the thickness of the 800MPa grade duplex steel is 2.5mm, and its matrix structure is a ferrite and martensite duplex structure with a martensite volume fraction of 33%.

[0055] Example 2:

[0056] A method for controlling the oxide layer at the reactive interface of thick 800MPa grade hot-dip galvanized duplex steel includes the following steps: Hot rolling process: A multi-stage hot rolling cooling process is adopted, with a heating temperature of 1240℃. Rough rolling is performed first, followed by finish rolling. The initial rolling temperature of rough rolling is 1100℃, and the final rolling temperature of finish rolling is 855℃. The coiling is carried out in two stages of water cooling. The first stage water cooling is reduced to 610℃, followed by air cooling to 556℃. The second stage water cooling is reduced to 225℃ before coiling. Rapid cooling causes structural separation between the oxide layer and the substrate, providing favorable conditions for subsequent pickling.

[0057] Pickling process: The belt speed is controlled at 83 m / min and the acid temperature is 83℃ to ensure complete removal of iron oxide scale and avoid over-pickling or under-pickling.

[0058] Pre-treatment process: The surface of the 800MPa grade duplex steel strip is cleaned to remove surface oil and impurities, and then dried. The drying temperature is controlled at 130℃ for 7 minutes to ensure that the surface of the strip is dry and clean.

[0059] Annealing and reduction process: The dried strip steel is fed into a continuous annealing furnace at a speed of 51 m / min. A gradient heating process is used, heating the strip steel to 800℃ at a heating rate of 17℃ / s, and then continuing to heat it to 835℃ at a heating rate of 4℃ / s, holding it at that temperature for 4 seconds to ensure complete austenitization of the duplex steel matrix. Subsequently, it is cooled to 695℃ at a cooling rate of 11℃ / s and held for 2.5 seconds to promote the uniform formation of the ferrite and martensite duplex structure. 16% hydrogen by volume is introduced into the annealing furnace for reduction, with the dew point controlled at -42℃. Nitrogen accounts for 84% of the volume. Precise atmosphere and temperature control reduces the holding time in the high-temperature range. A pre-oxidation process is added, with a pre-oxidation gas flow rate of 16.5 m³ / h, consisting of a nitrogen-oxygen mixture. The humidification dew point is set to -7℃, and the grate dew point is set to -28℃.

[0060] Hot-dip galvanizing reaction process: The annealed strip steel is quickly immersed in molten zinc liquid, the temperature of which is controlled at 460℃, and the immersion time is controlled at 5s. The composition of the zinc liquid by weight percentage is: zinc 99.52%, aluminum 0.22%, lead ≤0.002%, and the remainder being unavoidable impurities. 35ppm of rare earth element La is added to the zinc liquid.

[0061] Post-processing: After the strip steel exits the zinc bath, it is purged with an air knife at a pressure controlled at 0.10 MPa and a distance of 12 mm between the air knife and the strip steel to remove excess molten zinc from the surface. It is then first air-cooled to 320°C at a rate of 17°C / s, and then water-cooled to room temperature at a rate of 38°C / s to complete the preparation of 800 MPa grade hot-dip galvanized duplex steel.

[0062] In this embodiment, the thickness of the 800MPa grade duplex steel is 3.0mm, and its matrix structure is a ferrite and martensite duplex structure with a martensite volume fraction of 28%.

[0063] Example 3

[0064] A method for controlling the oxide layer at the reactive interface of thick 800MPa grade hot-dip galvanized duplex steel includes the following steps: Hot rolling process: A multi-stage hot rolling cooling process is adopted, with a heating temperature of 1238℃. Rough rolling is performed first, followed by finish rolling. The initial rolling temperature of rough rolling is 1095℃, and the final rolling temperature of finish rolling is 850℃. The coiling is carried out in two stages of water cooling. In the first stage, the temperature is cooled to 610℃ by water cooling and then to 552℃ by air cooling. In the second stage, the temperature is cooled to 230℃ by water cooling before coiling. Rapid cooling causes structural separation between the oxide layer and the substrate, providing favorable conditions for subsequent pickling.

[0065] Pickling process: The belt speed is controlled at 80m / min and the acid temperature is 85℃ to ensure complete removal of iron oxide scale and avoid over-pickling or under-pickling.

[0066] Pre-treatment process: The surface of the 800MPa grade duplex steel strip is cleaned to remove surface oil and impurities, and then dried. The drying temperature is controlled at 145℃ for 5.5 minutes to ensure that the surface of the strip is dry and clean.

[0067] Annealing and reduction process: The dried strip steel is fed into a continuous annealing furnace at a speed of 52 m / min. A gradient heating process is used, heating the strip steel to 815℃ at a heating rate of 19℃ / s, and then continuing to heat it to 845℃ at a heating rate of 5℃ / s, holding it at that temperature for 3.5s to ensure complete austenitization of the duplex steel matrix. Subsequently, it is cooled to 700℃ at a cooling rate of 12℃ / s and held for 2s to promote the uniform formation of the ferrite and martensite duplex structure. 18% hydrogen by volume is introduced into the annealing furnace for reduction, with the dew point controlled at -44℃. Nitrogen accounts for 82% of the volume. Precise atmosphere and temperature control reduces the holding time in the high-temperature range. A pre-oxidation process is added, with a pre-oxidation gas flow rate of 17.5 m³ / h, consisting of a nitrogen-oxygen mixture. The humidification dew point is set to -9℃, and the grate dew point is set to -26℃.

[0068] Hot-dip galvanizing reaction process: The annealed strip steel is quickly immersed in molten zinc liquid, the temperature of which is controlled at 458℃, and the immersion time is controlled at 4.5s. The composition of the zinc liquid by weight percentage is: zinc 99.48%, aluminum 0.25%, lead ≤0.002%, and the remainder being unavoidable impurities. 45ppm of rare earth element La is added to the zinc liquid.

[0069] Post-processing: After the strip steel exits the zinc bath, it is purged with an air knife at a pressure controlled at 0.09 MPa and a distance of 13 mm between the air knife and the strip steel to remove excess molten zinc from the surface. It is then first air-cooled to 340°C at a rate of 19°C / s, and then water-cooled to room temperature at a rate of 40°C / s to complete the preparation of thick-gauge 800 MPa grade hot-dip galvanized duplex steel.

[0070] In this embodiment, the thickness of the 800MPa grade duplex steel is 3.5mm, and its matrix structure is a ferrite and martensite duplex structure with a martensite volume fraction of 38%.

[0071] This invention achieves effective control over the oxide layer at the reaction interface of 800MPa grade hot-dip galvanized duplex steel through hot rolling gradient cooling, gradient annealing reduction, and precise atmosphere control. Specific technical effects are as follows: 1. Suppressing the formation of harmful oxide layers: By controlling the temperature gradient in the thickness direction of the strip to form surface compressive stress, the enrichment of Si and Mn elements on the surface is effectively suppressed, avoiding the formation of continuous oxide films and obtaining a thin and dense aluminum-containing suppression layer.

[0072] 2. Significantly improved coating adhesion: A uniform and dense pre-reduction layer is formed on the surface of the strip steel, which inhibits the disorderly growth of the oxide layer from the source.

[0073] 3. Good microstructure uniformity: The matrix is ​​a dual-phase microstructure of ferrite and martensite, with the volume fraction of martensite controlled at 20-40%, ensuring a balance between strength and plasticity.

[0074] 4. High process stability: The parameters of each process are precise and controllable, making it suitable for the industrial continuous production of products with a thickness of 2.5 to 3.5 mm.

[0075] 5. Compared with conventional methods, the method of the present invention can significantly reduce the enrichment of Mn elements at the reaction interface, obtain a continuous, uniform and dense interface inhibition layer, and comprehensively improve the surface quality and service performance of the product.

Claims

1. A method for controlling the oxide layer at the reactive interface of 800MPa grade hot-dip galvanized duplex steel, characterized in that, Includes the following steps: 1) Hot rolling: A multi-stage hot rolling cooling process is adopted; The hot rolling process involves heating at a temperature of 1200–1250°C, followed by rough rolling and then finish rolling. The initial rough rolling temperature is 1070–1120°C, and the final finish rolling temperature is 840–860°C. The coiling is achieved through two stages of water cooling. The first stage involves water cooling to 600–620°C, followed by air cooling to 550–560°C, and the second stage involves water cooling to 200–240°C before coiling. 2) Pickling: belt speed is 80-85 m / min, acid temperature is 82-85℃; 3) Pretreatment: The strip steel is surface cleaned and dried at a temperature of 120-150℃ for 5-8 minutes. 4) Annealing and Reduction: The strip steel is fed into a continuous annealing furnace at a speed of 50–52 m / min. A gradient heating process is adopted, first heating to 780–820℃ at 15–20℃ / s, then heating to 820–845℃ at 3–5℃ / s, and holding for 3–5 s; subsequently cooling to 690–700℃ at 10–12℃ / s, and holding for 2–3 s; 15%–18% H2 and 82%–85% N2 by volume are introduced into the furnace, and the dew point is controlled at -40℃ to -45℃; then it enters the pre-oxidation stage, using a nitrogen-oxygen mixed gas with a flow rate of 15–18 m³ / min. 3 / h, the humidification dew point is set to -5℃~-10℃, and the grate dew point is set to -25℃~-30℃; 5) Hot-dip galvanizing: The annealed strip steel is immersed in molten zinc at a temperature of 455-465℃ for 4-6 seconds. The chemical composition of the zinc liquid, by weight percentage, includes: Zn≥99.5%, Al 0.20%~0.25%, Pb≤0.003%, and also contains 30~50ppm of rare earth element La, with the balance being unavoidable impurities; 6) Post-treatment: Air knife purging is used, with an air knife pressure of 0.08-0.12 MPa and a distance of 10-15 mm between the air knife and the strip. Then, air cooling is performed at a rate of 15-30℃ / s to 300-350℃, followed by water cooling at a rate of 30-50℃ / s to room temperature. The chemical composition of the hot-dip galvanized duplex steel, by weight percentage, includes: C: 0.11%~0.15%, Mn: 1.70%~2.00%, Si: 0.35%~0.50%, P≤0.025%, Cr: 0.35%~0.52%, Nb: 0.015%~0.026%, Als: 0.020%~0.038%, balance Fe.

2. The method for controlling the oxide layer at the reaction interface of thick 800MPa grade hot-dip galvanized duplex steel according to claim 1, characterized in that, The thickness of the hot-dip galvanized duplex steel sheet is 2.5 to 3.5 mm.

3. The method for controlling the oxide layer at the reaction interface of thick 800MPa grade hot-dip galvanized duplex steel according to claim 1, characterized in that, The microstructure of the hot-dip galvanized duplex steel is a ferrite-martensite dual-phase structure, with a martensite volume fraction of 20% to 40%.

4. The method for controlling the oxide layer at the reaction interface of thick 800MPa grade hot-dip galvanized duplex steel according to claim 1, characterized in that, The nitrogen-oxygen mixture contains, by volume percentage: 20%–25% oxygen, with the remainder being nitrogen and unavoidable impurity gases.

Citation Information

Patent Citations

  • High-strength hot-galvanized dual-phase steel and preparation method thereof

    CN105483535A

  • Preparation method capable of simultaneously producing continuously-annealed and galvanized DP780 dual-phase steel

    CN114574674A